Room temperature visible/infrared emission and energy transfer in Nd3+-based organic/inorganic hybrids - Sá Ferreira, R. A.; Carlos, L. D.; De Zea Bermudez, V.; Molina, C. [UNESP]; Dahmouche, K. [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Springer Nature, 2003)
The photoluminescence features and the energy transfer processes of Nd3+-based siloxanepoly(oxyethylene) hybrids are reported. The host matrix of these materials, classed as di-ureasils, is formed by a siloxane backbone covalently bonded to polyether chains of two molecular weights by means of urea cross-links. The room-temperature photoluminescence spectra of these xerogels show a wide broad purple-blue-green band (350-570 nm), associated with the emitting centres of the di-ureasil host, and the typical near infrared emission of Nd3+ (700-1400 nm), assigned to the 4F3/2 → 4I9/2,11/2,13/2 transitions. Self-absorptions in the visible range, resonant with intra-4f3 transitions, indicate the existence of an energy conversion mechanism of visible di-ureasil emission into near infrared Nd3+ luminescence. The existence of energy transfer between the di-ureasil's emitting centres and the Nd3+ ions is demonstrated calculating the lifetimes of these emitting centres. The efficiency of that energy transfer changes both with the polymer molecular weight and the Nd3+ concentration.
Keywords: Di-ureasils; Energy transfer; Luminescence; Neodymium triflate; Crosslinking; Neodymium compounds; Photoluminescence; Polyethers; Silicon compounds; Thermal effects; Urea; Optical amplification; Sol-gels